2008
DOI: 10.1590/s0037-86822008000200010
|View full text |Cite
|
Sign up to set email alerts
|

O megaesôfago tratado cirurgicamente: perfil epidemiológico dos pacientes operados no Hospital de Clínicas da Universidade Estadual de Campinas entre 1989 e 2005

Abstract: A tripanossomíase americana descrita por Carlos Chagas em 1909 constitui, ainda hoje, um problema sócio-econômico nacional e regional que aflige, principalmente, os países do cone sul da América, prevalentemente. O nível endêmico decorreu, principalmente, devido à domiciliação dos vetores motivada por más condições de habitação, esgotamento de fontes alimentares ABSTRACTMegaesophagus is one of the manifestations of Chagas disease and surgical treatment is the approach that presents the best results. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 7 publications
3
18
0
1
Order By: Relevance
“…Regurgitation, halitosis, pyrosis and chest pain were present in more than 60% of the cases. Other epidemiological studies 7,19,21 have reported similar symptoms.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Regurgitation, halitosis, pyrosis and chest pain were present in more than 60% of the cases. Other epidemiological studies 7,19,21 have reported similar symptoms.…”
Section: Discussionsupporting
confidence: 61%
“…In 2 previous studies that were also performed in Goiás, Rezende 13 and Rezende and Luquetti 18 also found a greater prevalence of CM patients in Groups II and III, as did Oliveira et al 19 in a study performed in Campinas. Therefore, a change in the proportion of patients in each of the CM groups has occurred, and there is a higher prevalence of patients in CM groups with less advanced disease and smaller dilation (Groups I and II).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Chagasic megaesophagus corresponds to at least 80% of cases submitted to surgical treatment in Brazil,16,22,23 unlike countries in the developed world where cases consist almost entirely of idiopathic achalasia24 and affect 1 in every 100,000 individuals 25. …”
Section: Discussionmentioning
confidence: 99%